Prognostic significance of low TSH concentration in patients with COVID-19 presenting with non-thyroidal illness syndrome - Gong, Jing (BMC Endocr Disord, 2021)
BACKGROUND: Low free triiodothyronine (FT3) levels are related to a poor prognosis deterioration in patients with COVID-19 presenting with non-thyroidal illness syndrome (NTI). This study was designed to explore whether free thyroxin (FT4) or thyroid stimulating hormone (TSH) levels affected the mortality of patients with COVID-19 presenting with NTI. METHODS: Patients with COVID-19 complicated with NTI who were treated at our hospital were included in this retrospective study. Patients were divided into low TSH and normal TSH groups, as well as low and normal-high FT4 group, according to the reference range of TSH or FT4 levels. The 90-day mortality and critical illness rates were compared among patients with low and normal TSH levels, as well as among patients with low FT4 levels and normal-high FT4 levels; in addition, differences in demographic and laboratory data were compared. A Kaplan-Meier analysis and Cox proportional hazards models were used to assess the associations of TSH and FT4 levels with mortality. RESULTS: One hundred fifty patients with low FT3 levels and without a history of thyroid disease were included, 68% of whom had normal FT4 and TSH levels. Critical illness rates (74.07% VS 37.40%, P = 0.001) and mortality rates (51.85% VS 22.76%, P = 0.002) were significantly higher in the low TSH group than in the normal TSH group. Although no significant difference in the critical illness rate was found (P = 0.296), the mortality rate was significantly higher in the low FT4 group (P = 0.038). Low TSH levels were independently related to 90-day mortality (hazard ratio = 2.78, 95% CI:1.42–5.552, P = 0.003). CONCLUSIONS: Low FT4 and TSH concentrations were associated with mortality in patients with COVID-19 presenting with NTI; moreover, low TSH levels were an independent risk factor for mortality in these patients.